2020
DOI: 10.3390/a13050119
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Electricity Prices: A Machine Learning Approach

Abstract: The electricity market is a complex, evolutionary, and dynamic environment. Forecasting electricity prices is an important issue for all electricity market participants. In this study, we shed light on how to improve electricity price forecasting accuracy through the use of a machine learning technique—namely, a novel genetic programming approach. Drawing on empirical data from the largest EU energy markets, we propose a forecasting model that considers variables related to weather conditions, oil prices, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Hence, the empirical results obtained reveal that the hypotheses included in the study are validated. These results are consistent with the current literature, e.g., [5,15,16,21,32,[52][53][54].…”
Section: Discussion and Policy Implicationssupporting
confidence: 93%
“…Hence, the empirical results obtained reveal that the hypotheses included in the study are validated. These results are consistent with the current literature, e.g., [5,15,16,21,32,[52][53][54].…”
Section: Discussion and Policy Implicationssupporting
confidence: 93%
“…Sheha et al presented various models for the proactive prediction of energy demand in entire cities [429]. Castelli et al focused on improving the accuracy of electricity price forecasting by employing machine learning techniques that combine standard regression techniques with genetic algorithms [430]. Additional studies on this topic can be found in [406,[431][432][433][434].…”
Section: Modeling the Energy Market: From Power Grid Data To Energy P...mentioning
confidence: 99%
“…Energy price forecasting became a hot topic, especially in the past few years. The deregulation of the electricity market increased significantly the need for the accurate forecast of electricity prices, since the quality of the forecast has high importance and makes big impact on the risk management and the pricenegotiation processes of the market participants [1]. On the other hand, with the increasing percentage of renewable energy sources in the system, trading strategy based on energy price forecast may influence the storage and control strategies, as well [6].…”
Section: Introductionmentioning
confidence: 99%